TEACHING AND LEARNING ENGLISH LANGUAGE BY DISTANCE EDUCATION (Academia Science Repository, 2023)
Distance learning has become an increasingly popular way to learn and teach foreign languages. With the advancement of technology, it is now possible for students and teachers to interact with each other from different parts of the world through various online tools and platforms. This article is aimed to clarify the possibilities of learning language through distance education.